Science teachers’ perspectives and prior practices for science centre visit: strategies development - Lungile Philisiwe Gumede; Patricia Photo (Disciplinary and Interdisciplinary Science Education Research)
Abstract In ongoing science education, utilising informal learning environments such as science centres has emerged as a crucial strategy to enhance learners’ engagement and understanding of complex scientific concepts. However, despite their evident benefits, out-of-school learning environments often fail to produce lasting improvements in learners’ understanding of scientific concepts, largely due to inadequate integration with classroom teaching and a lack of strategic planning. This qualitative study, grounded in a moderate constructivist framework, investigates the perspectives of high school science teachers regarding the significant influence and strategic optimization of science centre visits. Through interviews and document analysis, informed by thematic analysis methodology, the study examines teachers’ perceptions and their prior practices when visiting the science centre. Teachers articulate a compelling narrative of how science centre visits serve as catalysts for active, experiential learning, and bridging the gap between theoretical knowledge and practical application. Furthermore, the study identifies and describes five strategic imperatives aimed at enhancing the effectiveness of science centre visits in science education. These imperatives encompass pre-visit curriculum integration, differentiated learning activities, teacher-led guided exploration, parental involvement, and continuous evaluation and improvement. Grounded in constructivist principles and contemporary educational theories, these strategies offer an inclusive framework to enrich learners’ learning experiences, cultivate their scientific curiosity, and foster a profound and enduring appreciation for the details of science. These findings highlight how crucial it is for teachers to have access to continual professional development opportunities and institutional support to enable them to fully utilise the pedagogical potential of science centre visits in science curricula.